Deconstructing the Seven Cs of Social Media: A Summative Perspective - Rautela, Sonica; Singhal, Tarun Kumar (International Journal of Interactive Mobile Technologies (iJIM), 2020)
One of the defining technological forces which are reshaping world today is the easy accessibility to the Internet. The Internet has changed the way people communicate with each other. Social media whose development was first marshaled by Web 2.0, has revolutionized the entire world of communication. The most intriguing fact is that the world of social media is constantly changing. The platforms which are topping the charts today may not be tomorrow. Also, it can be observed that the power has shifted from the hands of marketers to the hands of users which in turn have empowered users. The objective of the present study is to explore the different facets of social media in detail. These facets form the base for the world of social media and can be referred to as the 7 Cs of social media. These seven Cs are - content, community, conversation, capital (social), culture, collaboration, and conversion respectively. With an enhanced understanding of all these Cs of social media, the study proposes a conceptual model depicting the relationship between these seven Cs and social media. Companies should analyze each of these Cs in detail and design their social media strategies accordingly. This will not only assure the efficient and effective use of social media but also will help managers to decide where and how to allot firm resources in a better fashion.